Cerebral infarction and risk factors in acute type A aortic dissection with arch branch extension. Issue 8 (21st July 2022) - Gong, Wenqing; Zhou, Ling; Shang, Lei; Zhao, Hongliang; Duan, Weixun; Zheng, Minjuan; Ge, Shuping
ABSTRACT: Objective: Stanford type A aortic dissection (AAD) may affect the supra‐aortic arteries, which are associated with acute ischemic stroke (AIS) or transient ischemic attack (TIA). This study aimed to investigate cerebral perfusion, the infarction incidence and risk factors in AAD patients. Methods: A total of 156 consecutive AAD patients were enrolled and divided into two groups according to whether the aortic arch branches were involved: the affected group ( n = 90) and the unaffected group ( n = 66). Clinical, echocardiographic/carotid Doppler data and cerebral infarction morbidity were compared between the groups. Independent predictors of 30‐day AAD mortality were identified through multivariable Cox regression, and perioperative risk factors were analyzed. Results: In total, 57.7% of AAD patients had aortic arch branch involvement. Abnormal Doppler waveforms were more common in the affected group ( p < 0.05). Regarding intracranial perfusion, the blood flow volumes (BFVs) of the bilateral internal carotid arteries (ICAs) and right vertebral artery (RVA) in the affected group were significantly reduced ( p < 0.05). The incidence of cerebral infarction in the affected group was significantly higher than that in the unaffected group (35.6% vs. 19.7%, p = 0.031). Multivariable analysis revealed that age >45 years old, right internal carotid artery (RICA) involvement and reduced left ventricular ejection fraction (LVEF) were significant predictors of perioperative death. Conclusions: Aortic arch branch involvement is common in patients with AAD and is associated with reduced cerebral blood flow (especially on the right side) and a higher incidence of cerebral infarction. Age, extension of the RICA dissection and LVEF impairment are independent risk factors for AAD‐related death.